2006
DOI: 10.1021/ma052754+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Star-Shaped Poly(ethylene-co-propylene) Polymers Bearing Terminal Self-Complementary Multiple Hydrogen-Bonding Sites

Abstract: The polymerization of isoprene was initiated with 3-(tert-butyldimethylsilyloxy)-1-propyllithium (TBDMSPrLi), which contained a silyl-protected hydroxyl functionality. Living poly(isoprenyllithium) with controlled molecular weight and narrow molecular weight distribution coupled efficiently with divinylbenzene to form well-defined star-shaped polymers. Both linear and star-shaped polymers were subsequently hydrogenated to poly(ethylene-co-propylene) and deprotected quantitatively to yield terminal primary hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 72 publications
3
39
0
Order By: Relevance
“…The results indicate that an effective semidilute concentration in the boundary layers with PEG molecular weight higher than several thousand g/mol rises above that of the bulk solutions. We found that the magnitude of the reductions in gyration radius, physical parameters of these PEG molecules or the rise in local concentration of PEGs at the Au/liquid interface is consistent with those documented in the literatures [36,[66][67][68][69][70][71].…”
Section: Resultssupporting
confidence: 90%
“…The results indicate that an effective semidilute concentration in the boundary layers with PEG molecular weight higher than several thousand g/mol rises above that of the bulk solutions. We found that the magnitude of the reductions in gyration radius, physical parameters of these PEG molecules or the rise in local concentration of PEGs at the Au/liquid interface is consistent with those documented in the literatures [36,[66][67][68][69][70][71].…”
Section: Resultssupporting
confidence: 90%
“…68 Furthermore, the group of van Hest showed the synthesis of nucleobase-functionalized block copolymers via atom-transfer radical polymerization of thymine, adenine, cytosine, and guanine nucleobase-functional methacrylates. 69,70 The quadruple hydrogen-bonding UPy-unit, developed in our group, has been further employed in the functionalization of several low molecular weight polymers, such as poly-(dimethylsiloxanes) (PDMS), 41,71 poly(ethylene butylenes) (PEB), [72][73][74] poly(ethers), 72,75,76 poly(carbonates), 72,77 poly-(styrenes) (PS), 78 poly(isoprenes) (PI), 78 poly(ethylene-copropylenes) (PE-co-PP), 79 and poly(esters) 28,72,80,81 (Table 1). a) The compound numbers correspond to the numbers in Fig.…”
Section: The Biomaterialsmentioning
confidence: 99%
“…Also, poly(ethylene-co-propylene) prepolymers were coupled to UPy-units. 79 Next to monofunctional PE-co-PP 7i, bifunctional polymers 6k and 6l and even a star-shaped structure 8e were synthesized. Trifunctional UPy-PEO-PPO copolymer 8a has been shown to assemble into supramolecular networks.…”
Section: 8082mentioning
confidence: 99%
“…In addition, a heat-exchange coil, a thermocouple, a septum sealed port, various stainless steel transfer lines to introduce solvent (cyclohexane), and inlet/vent for purified nitrogen were equipped to the anionic reactor. [27,28] The anionic reactor system was maintained at a constant nitrogen pressure (40 psi). The 600 mL-capacity anionic polymerization reactor was filled with cyclohexane (300 mL).…”
Section: Synthesis Of Liquid 60 Mol-% Poly(buta-12-diene)s Via Livinmentioning
confidence: 99%